Education for Capability in Medicine - Salam, Abdus; Akter, Shaima; Salam, Md Wasek; Yusoof, Mahmood Bin Abu; Abdelhalim, Abdelbaset Taher; Al Mahmood, Abu Kholdun (International Journal of Human and Health Sciences (IJHHS), 2025)
Abstract not available International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 71-74